Armenian Plans for the Violent Annexation of Georgian Lands under the Dashnak Government - Putkaradze, Tamaz; Putkaradze, Nani (International Scientific-practical Conference: „Modern Challenges and Achievements in Information and Communication Technologies“ Transactions, 2026)
After the bourgeois-democratic revolution of February 1917, the Russian Empire collapsed. The three republics of the Caucasus were united into a single Transcaucasian Federal-Democratic Republic. But its existence was short-lived. Soon, the Federal Republic disintegrated, and on its ruins, three states emerged almost simultaneously. Immediately after the emergence of independent states, there was a need to separate the borders, but the Dashnak government's unfounded territorial claims and the attempt to violently annex Georgian lands led to the conflict known in history as the Armenian-Georgian war. The aim of this paper is to show the groundlessness of the Armenian government's territorial claims based on historical sources, scientific literary data, the tendentious nature of the works of Armenian authors published on this topic, and an attempt to present history in a crooked prism. The methodological basis of the research is the universal scientific principles of objectivity, comprehensiveness and systematicity, historical-comparative and historical-typological methods. Конец формы